Penerapan Model Pembelajaran Teams Games Tournament untuk Meningkatkan Kecerdasan Interpersonal Siswa Kelas IV pada Mata Pelajaran IPAS - Safinatunnajah Safinatunnajah; Supriansyah Supriansyah (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
If a nation wants to advance and prosper, education is a must. Since a nation's educational level is a good proxy for its overall development, This study aims to shed light on how fourth grade science students may benefit from enhancing their interpersonal intelligence via the use of the team games tournament learning paradigm. Classroom action research is used in this sort of study. Planning, doing, watching, and reflecting are the four pillars of the action intervention design. Field notes, documentation, surveys, and observation were the methods of data gathering. Research tools for students' interpersonal intelligence and measures to evaluate instructor and student activities were among the data sets assessed by researchers using data analysis methods. This study's findings demonstrate that students' interpersonal intelligence is substantially enhanced by the implementation of the TGT paradigm. Data is examined and understood in each cycle via the use of graphs and tables that display the overall outcomes and percentages for that cycle. If the percentage results of the teacher and student observation sheet instruments in using the TGT model during scientific learning achieve a minimum of 80% and 80% of the total students acquire an interpersonal intelligence questionnaire score of 70 or above, then the study is considered successful. According to the data analysis findings, which demonstrated a rise in the proportion of students' and instructors' interpersonal intelligence and the monitoring steps taken, the anticipated goal success indicators were met in cycle II. The fourth graders at SDN Tugu Utara 17 Pagi have a lot of room to grow in their interpersonal intelligence with the help of a TGT-type cooperative learning approach.